TRANSNATIONAL COMPARATIVE FRAMING ANALYSIS OF SOUTH CHINA SEA CONFLICT IN SOUTHEAST ASIAN ONLINE MEDIA COVERAGE - Paundria Dwijastuti; S. Rouli Manalu (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
The objective of this study is to analyze the framing of the South China Sea conflict. This research focused on forty publications of four online media in Southeast Asia; The Jakarta Post, The Inquirer Philippine, The Star Online, and VietnamPlus as the representatives of the media on the coverage of the South China Sea dispute. The approach used in this study is a framing analysis, specifically with Guo’s method of the Transnational Comparative Framing Model. Basing on the theories of peace and war journalism, this study hypothesized that the four online media in Southeast Asia incline toward war journalism. This result of the framing analysis found that the media in Southeast Asia affirm the main assumption of the research, showing that the media in Southeast Asia opted for the war journalism in covering the news about the South China Sea conflict. There are four main indicators which represent the war journalism which include: elite-oriented, victory-oriented, propaganda-oriented, and partisan coverage. This study also showed that the media in Southeast Asia mostly cover the conflict through the lens of territorial dispute frame. This study affirmed the applicability of the theories and findings previous studies. From a media perspective, this study emphasized the need to take into account the importance of peace journalism practice during a conflict.